The Company of Neighbours : Revitalizing Community Through Action-Research - Banks, C. Kenneth (Charles Kenneth), 1940- (Book collections on Project MUSE., 1999)
The town of Hespeler in southwestern Ontario is an old industrial community that lost its core manufacturing businesses, its municipal status, and its civic pride in the time since the end of the Korean War. In the early 1990s, Banks and Mangan implemented a community-development, action-research project designed to rebuild and revitalize the town. This book illustrates the success of local citizens in the revival of their community and the discovery of a nascent network of mutual support among neighbours. The authors demonstrate how inquiry, education, and action-research can combine to form an effective model for engaged ethnographic analysis. Their application of narrative inquiry to community-based research is new, and their conclusion that externally generated, imposed structure impedes community autonomy and responsibility is well supported. The book significantly expands the established theoretical framework of action-research and offers an exciting alternative to existing models of community development. The Company of Neighbours demonstrates a valuable approach for researchers, social workers, educators, and geographers in facilitating the collective efforts of people in local communities to shape the conditions of their own lives. With a new farmer's market, a museum in the renovated train station, youth programs, and an invigorated Business Improvement Association, Hespeler is well on its way to a new identity.